Detecting Warming Trends and Climate Regime Transitions Using Satellite-Derived Temperature Data in Northeast India (European Journal of Pure and Applied Mathematics, 2025)
There are growing indications that Northeast India is feeling the effects of climate change, but in-depth studies on temperature shifts across the region are still quite limited. In this work, we looked at how both annual and seasonal mean temperatures have changed at 14 different locations between 1990 and 2024, using satellite data. To get a well-rounded understanding, we applied several statistical methods to capture not just long-term warming but also any sudden changes in temperature patterns. The Mann-Kendall and modified Mann-Kendall tests pointed to noticeable warming in number of locations, and Sen’s slope helped us measure how quickly these changes are taking place. We also used the innovative trend analysis to catch more complex, non-linear trends, and the percent bias method showed that recent decades have generally been warmer than the earlier ones. Among the 14 sites, places like Guwahati, Dibrugarh, and Cherrapunji stood out for clear warming trends, especially during the monsoon and winter months. Change point detection tools like the Pettitt and Buishand tests highlighted major shifts around 2012–2013 in several areas. At the same time, stations such as Agartala and Aizawl showed more gradual warming, but the upward trend was still evident. These results make it clear that warming is unfolding in different ways across the region sometimes gradually, sometimes in sharp jumps. Understanding these local patterns is essential for developing effective responses to climate-related risks in this ecologically and climatically sensitive part of India.